STRATEGI KOMUNIKASI PT PEGADAIAN(Persero) CABANG PASAR KODIM PEKANBARU DALAM MENARIK MINAT CALON NASABAH - Ristua, Yohanna; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The communication strategy is determining the success of effective communication activities. PT. Pegadaian (Persero) Cabang Pasar Kodim Pekanbaru is one of the State-Owned Enterprises (SOEs) need to communicate or to inform its products and services to the community so that people can recognize and be motivated to use the products and services offered pawn. Based on this, the identification of the issues examined in this study is how the communication process PT. Pegadaian (Persero) Cabang Pasar Kodim Pekanbaru, what kinds of messages conveyed and any media used in attracting prospective customers as well as any obstacles encountered in attracting prospective customers. The usefulness of this study as an evaluation for PT. Pegadaian (Persero) in implementing socialization strategies in order to achieve high public participation.This study uses descriptive qualitative study conducted in PT. Pegadaian (Persero) Cabang Pasar Kodim Pekanbaru located in Jl. Teratai No. 92 Pasar Kodim Pekanbaru-Riau, with the selection of informants using the technique of accidental, and also using purposive sampling technique. The object of this study is the communication strategy PT. Pegadaian with research subjects include customers, prospective customers, branch leaders, and employees. Data collection techniques used were interviews, observation, and documentation.The results obtained indicate that communication strategies PT. Pegadaian (Persero) Cabang Pasar Kodim Pekanbaru performed using marketing communication in various forms consisting of product, price, promotion and place. So the researchers came to the conclusion that the concept has been defined using a marketing communications strategy. Messages obtained in promoting the benefit that the process is easy and takes about 15 minutes pawn goods can be processed and secure storage, because if we are pawning in PT. Pawnshop (Persero) we should not be afraid pawned goods are not returned home following the prescribed procedure, as well as any warranties or goods that have been pawned it will be insured, if PT Pegadaian (Persero) Cabang Pasar Kodim Pekanbaru there is something unexpected happens concerning the goods then asuransilah will replace the pawn goods, also taking referrals, banners, brochures, signposts and electronic media to promote their products. Keywords: Communications Strategy, Marketing Communications Strategy, Promotions